低技术型劳工输入新加坡 ： 社会层面的分析 = The analysis of the Social aspects of migratory labour : with reference to the low skilled labour in Singapore - 林绍杰 Lim, Shao Jie (2015)
全球化这个概念自二十一世纪初已经成为了流行术语。而全球化所带来的其中一种趋势，便是 海外移民。大量的人移居海外，标志着不同国家、经济体、文化以及个人层面上的交流。世界经济 在全球化的推动下，生产不断的国际化，而国际分工也不断的加强。劳动力便是首要的生产要素，它 可以通过世界范围内流动得到重新配置，调节劳动资源。 新加坡自独立以来，为了提高国家的竞争水平和人民的生活素质，在第一个十年便奠定了经济基础，成为自由经济体，并致力于国家基础设施的建设。从二十世纪七八十年代起，新加坡进入了工业化时期。九十年代至今，新加坡经济发展则转向高科技、金融业和服务业。然而，服务业和建筑业的职位空缺仍较多。为了保持经济持续发展，新加坡政府放宽对外来劳工的限制。例如，新加坡的建筑业主要依赖外国劳工，2014 年就雇佣了约三十二万的外籍劳动力。 本文首先将尝试透过亚当·斯密的“分工理论”，探讨分工如何能提高劳动生产率和发展国家经济。而大卫·李嘉图的“比较优势理论”则进一步探讨了商业自由制度下如何更有效的利用劳动来促进国家贸易。这些理论都直接或间接的提到了劳动力的调配对国家的利益。随着全球化趋势的进展，劳务输出也被视为资本经济体系的普遍现象。而许多关于劳动力或劳务输出的研究都着重于它们对经济发展的影响，在一定的程度上忽略了社会层面的分析，而这，便是本文分析的要点。 本文试探讨外籍劳工在东南亚，尤其是新加坡的现状。作为一个对外开放的自由经济体，新加 坡高度的依赖外籍劳工来持续发展。但对于低技术型工作的劳工，新加坡政府实施了严谨的管理条例。2013 年小印度骚动事件，促使社会对低技术型工作劳工进行了重新的探讨，开始把注意力转向社会层面的分析。最后，本文就新加坡的印度籍和孟加拉籍劳工为研究对象，透过社会层面的角度分析他们和新加坡人的互动。Globalization has been a favourite catchphrase since the turn of the century. It has overseen the phenomenon of global migration and the ever growing interconnectedness in the realm of politics, culture, communication and technologies around the world. Globalization has spurred the development of the world economy through the internationalization of production and the mobility of manpower is a key factor. This mobility ensures that manpower is allocated efficiently and helps improve productivity Singapore since its independence has always aimed to increase its economic competiveness and by growing the economy, achieve a high standard of living for its people. In its early years, focus was on restructuring to become a free economy and the building of basic infrastructure. Singapore became industrialized in the 1970s and from the 1990s till present, its economic focus shifted to that of the biomedical, financial and service industry. The construction and service industry faced a lack of manpower and in bid to resolve this, foreign manpower regulations were loosened. In 2014, the construction industry alone saw the employment of approximately 320000 foreign labourers. This paper shall analyse Adam Smith’s “Division of Labour” theory as well as David Ricardo’s theory of Comparative Advantage in an attempt to show how the division of labour improves productivity and how efficient manpower distribution improves economic trade among nations. What is of interest here is the overwhelming focus on the economic benefits brought about by labour mobility for nations. Studies have，to a certain extent neglected the social aspects of migrant labour, of their lives and interactions with the host nation and society. This is what the paper hopes to shift the focus to. The paper will then focus on Singapore as it is not only a free economy, but it is also one that is extremely dependent on foreign labour to sustain its growth. It is interesting to note that strict regulations govern the use of foreign labours pertaining to low skilled jobs. The Little India Riot in 2013 saw the revaluation of economic concerns to include that of the social aspects and demands of foreign labourers as well as their interactions with the society. Interviews with foreign labourers were also done to better understand their perspectives on interactions with the Singaporean society.